A review of literature on urban sprawl using bibliometric technique - Rosni, Nur Aulia; Hj. Mohd. Noor, Norzailawati; Ponrohono, Zakiah (Kulliyah of Architecture and Enviromental Design, International Islamic University Malaysia, 2018)
Urban sprawl is the broad research topic in urban studies. Thus far, the debate on the causes and consequences of urban sprawl has not led to a widely accepted interpretative framework. This paper attempts to review publications on urban sprawl factors and causes extracted from two largest scientific databases namely Scopus and ScienceDirect. The time of publication was set from 1996 to 2015 with 20 years’ gap. The citation-based approach analysis was used to provide better vision regarding this topic where the journal articles are selected by using identified keywords from wide-ranging fields that cover built environment, geography, planning, architecture, engineering, economics, transportation, health, social and spatial technologies.